When Research Doesn’t Look Like Research: Faculty Development for Creative Artists - Mechele Leon; Tamara Falicov; Michelle Hayes; Mary Anne Jordan (Academic Chairpersons Conference Proceedings, 2015)
Faculty in the creative arts face unique challenges when it comes to the recognition of their productivity. How do we develop and assess creative works when print publication is the standard measure of accomplishment? This collaborative roundtable offers academic leaders insight about developing and assessing the work of faculty artists.
Keywords: Assessment; Artists; Arts; Creative; Publication